Absence of lysogeny in wild populations of Erwinia amylovora and Pantoea agglomerans - Roach, Dwayne R (Microb Biotechnol, 2015)
Lytic bacteriophages are in development as biological control agents for the prevention of fire blight disease caused by Erwinia amylovora. Temperate phages should be excluded as biologicals since lysogeny produces the dual risks of host resistance to phage attack and the transduction of virulence determinants between bacteria. The extent of lysogeny was estimated in wild populations of E. amylovora and Pantoea agglomerans with real–time polymerase chain reaction primers developed to detect E. amylovora phages belonging to the Myoviridae and Podoviridae families. Pantoea agglomerans, an orchard epiphyte, is easily infected by Erwinia spp. phages, and it serves as a carrier in the development of the phage-mediated biological control agent. Screening of 161 E. amylovora isolates from 16 distinct geographical areas in North America, Europe, North Africa and New Zealand and 82 P. agglomerans isolates from southern Ontario, Canada showed that none possessed prophage. Unstable phage resistant clones or lysogens were produced under laboratory conditions. Additionally, a stable lysogen was recovered from infection of bacterial isolate Ea110R with Podoviridae phage ΦEa35-20. These laboratory observations suggested that while lysogeny is possible in E. amylovora, it is rare or absent in natural populations, and there is a minimal risk associated with lysogenic conversion and transduction by Erwinia spp. phages.